2011
DOI: 10.1021/ed100622h
|View full text |Cite
|
Sign up to set email alerts
|

Argument-Driven Inquiry: An Introduction to a New Instructional Model for Use in Undergraduate Chemistry Labs

Abstract: This article presents a new instructional model called Argument-Driven Inquiry (ADI) that can be used in undergraduate college chemistry laboratory courses. ADI is designed to provide students with an opportunity to develop their own method to generate data, to carry out investigations, use data to answer research questions, write, and be more reflective as they work. In addition, the ADI instructional model integrates opportunities for students to engage in scientific argumentation and peer review. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 34 publications
3
107
1
6
Order By: Relevance
“…The current study also shows that after argumentation training, students' argumentation skills had statistically changed. In Walker et al (2010), it was found that after the study applied the ADI method, there was a significant difference between students using the ADI method and those using the traditional laboratory method regarding their use of evidence and reasoning skills. But unlike these studies, Osborne et al (2004) found no significant difference between the groups at the end of the study in terms of argumentation levels.…”
Section: Discussion On the Argumentation Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study also shows that after argumentation training, students' argumentation skills had statistically changed. In Walker et al (2010), it was found that after the study applied the ADI method, there was a significant difference between students using the ADI method and those using the traditional laboratory method regarding their use of evidence and reasoning skills. But unlike these studies, Osborne et al (2004) found no significant difference between the groups at the end of the study in terms of argumentation levels.…”
Section: Discussion On the Argumentation Levelmentioning
confidence: 99%
“…It was believed that this study could help individuals with difficulties in scientific inquiry, argumentation, and their use in the classroom by providing information about scientific inquiry and argumentation. Although science laboratory practices aim to provide concrete experiences, activate experiential learning, increase student knowledge, and provide meaningful and permanent learning, the "cookbook" approach in traditional laboratory practices hinders science classes from reaching their goals (Hoffstein & Lunetta, 2004;Schen, 2007;Walker, Sampson, Grooms, Anderson, & Zimmerman, 2010). Similarly, the traditional deductive laboratory approach which explicitly gives information on how to carry out an experiment, collect and analyze the data, and indirectly tells what results should be found in relation to the theoretical knowledge is also widely used in Turkey (Aydoğdu & Ergin, 2008;Feyzioğlu et al, 2011;Yağbasan & Kanlı, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Students are given information on how to do this type of experiment. Most of the time they do not even think about the steps (Hofstein et al, 2008;Hofstein & Lunetta, 2004;Walker, Sampson, Grooms, Anderson, & Zimmerman, 2010;Walker, Sampson, Grooms, & Zimmerman, 2011;Walker, 2011).…”
Section: Introductionmentioning
confidence: 99%